Trade liberalization and labor markets in developing countries: Theory and evidence - Jorge Saba Arbache (Institute for Applied Economic Research (ipea), 2015)
The aim of this paper is to present a review of the theoretical and empirical literature about the effects of trade liberalization on the labor markets of developing countries. We discuss models which seek to explain the empirical finding that openness has increased the wage inequality in several developing countries.
Keywords: 330